IMPLEMENTASI PEMBELAJARAN TEMATIK DI KELAS V MADRASAH IBTIDAIYAH PERSATUAN UMAT ISLAM MEKARJATI HAURGEULIS - Jundan Al Salam Aldin; Henri Peranginangin Tanjung; Abdur Rahim (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2023)
Thematic Learning is part of the curriculum of the Madrasah Ibtidaiyah Persatuan Ummat Islam (PUI) Mekarjati, Haurgeulis, Indramayu; is a learning model using a theme as a hook for several subjects into a single unit, taught to fifth grade students. The purpose of teaching the thematic learning model is to be able to provide meaningful experiences for students, but in practice the teacher still has not carried out thematic learning as it should. The objectives of the study were to find out (a) the implementation of thematic learning in the fifth grade of Madrasah Ibtidaiyah PUI Mekarjati, Haurgeulis, and (b) the extent of the obstacles to the implementation of thematic learning in the fifth grade of Madrasah Ibtidaiyah PUI Mekarjati, Haurgeulis. This research was conducted using a qualitative (descriptive) approach using the methods (a) interviews of researchers with teachers and related parties, (b) classroom observations on the learning process in the classroom from the beginning to the end of learning and (c) documentation of the learning process in the classroom. While the data analysis technique used is the data triangulation technique, namely to check the validity of the data. The results showed that the implementation of thematic learning in class V Madrasah Ibtidaiyah PUI Mekarjati Haurgeulis consisted of three stages, namely the learning planning stage, the implementation stage of the learning process and the learning evaluation stage. At the planning stage, the learning is in accordance with the standards or the 2013 curriculum. At the stage of the thematic learning implementation process in class V, the teacher has not fully implemented the thematic learning by referring to the Learning Implementation Plan (RPP) that has been made previously. At the learning evaluation stage, the teacher uses authentic assessment in accordance with the reference provisions in the 2013 curriculum. The obstacles faced in thematic learning in class V Madrasah Ibtidaiyah PUI Mekarjati Haurgeulis are the limited knowledge of teachers in the application of thematic learning models, and inadequate school infrastructure adequate. The solution taken is to prepare lesson plans together in KKG activities, and maximize the use of existing facilities and infrastructure for the implementation of thematic learning.